Statistical analysis of the pulse propagation in free space optic - Yap D.F.W.; Tahir M.A.E.M.; Koh S.P.; Tiong S.K. (2023)
Even though free space optic (FSO) has the capacity to go beyond the limit of fiber optics but unfortunately FSO suffers a few limitations caused by its transmission medium, the atmosphere. Thus, detail research is needed to study the ciharacteristic of free space optic so as to improve the system subsequently. Simulation using measured parameters is important to gain certain understanding and some level of estimation regarding the pulse behavior in free space. MATLAB was used as the simulation platform for this study. With the help of sufficient experimental or measured parameter, an accurate model can be obtained and analyzed. This will allow some level of prediction on the behavior of the propagating light pulse in the atmosphere and enable further improvement of the FSO performance.